2007
DOI: 10.1111/j.1600-051x.2007.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the CD14 and IL‐6 genes associated with periodontal disease

Abstract: According to the present results, an evident association exists between the carriage of the T-containing genotype of CD14(-260) and the GG genotype of IL-6(-174) and the extent periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 41 publications
6
91
0
6
Order By: Relevance
“…However, the results of studies on the associations between these polymorphism and clinical forms of periodontitis are contradictory (13,19,32,33). In a study (30), that was performed to compare the frequencies of cytokines (CD14, IL-6, TNF-alfa, IL-10, TLR-4) genotypes in patients with CP, was found that an evident association only exists between T genotypes of CD14 (-260) and the GG genotype of IL-6 (-174), and the extent of periodontal disease. Similar to our findings, the study by Nibali et al (33), which involved 224 AP patients and 231 controls, revealed that the -174 G allele is significantly associated with an increased risk of AP.…”
Section: Genotypes and Alleles Distribution Of Polymorphisms In The Nmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of studies on the associations between these polymorphism and clinical forms of periodontitis are contradictory (13,19,32,33). In a study (30), that was performed to compare the frequencies of cytokines (CD14, IL-6, TNF-alfa, IL-10, TLR-4) genotypes in patients with CP, was found that an evident association only exists between T genotypes of CD14 (-260) and the GG genotype of IL-6 (-174), and the extent of periodontal disease. Similar to our findings, the study by Nibali et al (33), which involved 224 AP patients and 231 controls, revealed that the -174 G allele is significantly associated with an increased risk of AP.…”
Section: Genotypes and Alleles Distribution Of Polymorphisms In The Nmentioning
confidence: 99%
“…However, in this study, IL-6 GG genotypes could not modify the risk of chronic periodontitis but increased the risk of aggressive periodontitis. Several studies have been published on whether the IL-6 polymorphism predisposes to periodontitis (29)(30)(31). However, the results of studies on the associations between these polymorphism and clinical forms of periodontitis are contradictory (13,19,32,33).…”
Section: Genotypes and Alleles Distribution Of Polymorphisms In The Nmentioning
confidence: 99%
“…In the present study, the lack of statistical significance in the linear regression test showed that the SNP -1082G/A of the IL-10 gene has no predictive value for periodontal disease. However, the authors reported a higher frequency of the genotype GG in individuals with periodontitis, suggesting that the G allele plays an important role in the course of periodontal disease (Scarel-Caminaga et al, 2004;Moreira et al, 2007;Tervonen et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…Periodontitis can occur when there is an imbalance between periodontopathogenic bacterial species and the host's defense, which is characterized by exacerbation of inflammatory and immunological reactions against the bacterial biofilm ( Andrade et al, 2013). Many studies have attempted to identify genetic polymorphisms in mediators of the immune response, such as those that have been considered to be potential susceptibility factors related to periodontal disease (Kornman et al, 1997;Moreira et al, 2007;Tervonen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…44 IL-1 gibi periodontitisin patogenezinde önemli role sahip olan TNF-α'nın gen polimorfizmi ile periodontitis arasındaki ilişkiyi değerlendiren çalışmalara göre TNF-α geninin allel sıklığı da IL-1 gibi farklı etnik toplumlarda çeşitlilik gös-termektedir. TNF-α gen polimorfizmi ile periodontitis arasında ilişki olduğunu belirten çalış-malara 47 karşın, ilişkinin olmadığını ileri süren çalışmalar da [47][48][49][50][70][71][72][73] bulunmaktadır. Periodontal hastalıkta etkili olabilen bir diğer antienflamatuvar sitokin de IL-10'nun promoter polimorfizmleridir.…”
Section: Peridontal Hastalıkta Genetik Faktörlerin Rolüunclassified